2018
DOI: 10.1002/adsc.201701463
|View full text |Cite
|
Sign up to set email alerts
|

Hydroaminomethylation in Aqueous Solvent Systems – An Efficient Pathway to Highly Functionalized Amines

Abstract: Tandem‐catalyzed hydroaminomethylation is a useful tool for synthesizing linear amines from olefins and amines in an atom‐efficient manner. To enable the coupling of highly functionalized, hydrosoluble amines with non‐water‐soluble olefins, this reaction must be transferred to aqueous biphasic solvent systems. In this work, we systematically evaluate reaction conditions to provide a selective hydroaminomethylation of 1‐octene with diethanolamine as model substrates. Although water is both the condensation side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Vorholt et al [161,162] reported a sustainable strategy for hydroaminomethylation, under aqueous biphasic conditions, using Rh/sulfoxantphos as catalyst, oct-1-ene as substrate and diethanolamine as nucleophile, at 100°C temperature and P(CO/H 2 1 : 3) = 50 bar, finding up to 85 % of olefin conversion after 6 h and 79 % selectivity for the desired amine (Table 3, entry 1).…”
Section: Hydroformylation/reductive Amination (Hydroaminomethylation)mentioning
confidence: 99%
See 1 more Smart Citation
“…Vorholt et al [161,162] reported a sustainable strategy for hydroaminomethylation, under aqueous biphasic conditions, using Rh/sulfoxantphos as catalyst, oct-1-ene as substrate and diethanolamine as nucleophile, at 100°C temperature and P(CO/H 2 1 : 3) = 50 bar, finding up to 85 % of olefin conversion after 6 h and 79 % selectivity for the desired amine (Table 3, entry 1).…”
Section: Hydroformylation/reductive Amination (Hydroaminomethylation)mentioning
confidence: 99%
“…However, reutilization studies for this catalyst were not reported. 1 Vorholt [162] Oct-1-ene (T = 100°C, P = 50 bar (CO/H 2, 1 : 3), 6 h)…”
Section: Hydroformylation/reductive Amination (Hydroaminomethylation)mentioning
confidence: 99%
“…Xantphos and its sulfonated, water-soluble variation sulfoXantphos are well known hydroformylation ligands that give high linear to branched ratios due to their wide bite angle (111°) and were successfully applied for hydroformylation reactions in the past. [32][33][34] We then focussed on finding a suitable catalyst for the aldol condensation step. Inorganic bases, such as sodium or potassium hydroxide are the most common catalysts in aldol reactions.…”
Section: Catalysis In Watermentioning
confidence: 99%
“…30,31 Furthermore, aqueous multiphase catalysis has been successfully used for catalyst recycling in the hydroaminomethylation tandem reaction. 32 While hydroformylation and aldol condensation alone have often been studied in liquid/liquid systems, to our knowledge, the tandem reaction has not been demonstrated in such a manner. In this work, we therefore set out to apply multiphase catalysis to perform the hydroformylation/aldol condensation tandem reaction with special focus on recycling of both catalysts simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Another example of this was the hydroaminomethylation of isoprene . The approach for the hydroaminomethylation of higher alkenes in aqueous solvent systems was yet only realized for a few selected examples on a small scale using additional surfactants, such as quaternary ammonium compounds, a cosolvent such as 1-butanol, macroligands to form a micellar system, rhodium nanoparticles, , or mass transfer agents (MTAs) such as cyclodextrins (CDs) . These examples are compared in more detail together with the results of this work in Table .…”
Section: Introductionmentioning
confidence: 99%